Redescription of the Siberian species Pardosa jeniseica (Araneae: Lycosidae) - Marusik, Yuri M. (Zootaxa, 2018)
The male of Pardosa jeniseica, collected in the East-Kazakhstan Area, was first illustrated in Eskov & Marusik (1995). The authorship of the species was given as “Zyuzin, 1991”, because A.A. Zyuzin informed the authors in 1990 that a description of the species was in press. Because no such description ever appeared the authorship was given to Eskov & Marusik, and a single male specimen from East-Kazakhstan is now considered to be the holotype. It is kept in Zoological Museum of the Moscow State University. Esyunin et al. (1999) illustrated and described a female from the Urals thought to be conspecific with P. jeniseica. Conspecifity of the illustrated specimen with P. jeniseica was doubted by Marusik et al. (2000). Kronestedt (2013) was the first to illustrate the epigyne of P. jeniseica and Azarkina & Trilikauskas (2013) provided both verbal and illustrated descriptions of the female, and its epigyne and endogyne. Both sexes taken from one locality were never depicted, nor was peculiar pubescence of the male’s leg I. Therefore, I decided to provide detailed illustrations and a verbal description of this species based on specimens from the place considered to be the type locality. Specimens were photographed at the Zoological Museum (University of Turku, Finland) with a Canon EOS 7D camera attached to an Olympus SZX16 stereomicroscope and a SEM JEOL JSM-5200 scanning microscope. Digital images were montaged using Helicon focus 3.10 image stacking software. All measurements are given in millimeters. The following abbreviations are used for leg segments: Fe femur, Pa patella, Ti tibia, Mt metatarsus, Ta tarsus; leg spination abbreviations: d dorsal, p prolateral, r retrolateral, v ventral. Material used in this study is deposited in the Moscow State University (ZMMU) and Zoological Museum of the University of Turku (ZMUT). I thank Seppo Koponen (Turku, Finland) for providing museum facilities and Don Buckle (Saskatoon, Canada) for editing English in the earlier draft of the manuscript.